2005
DOI: 10.1002/pros.20188
|View full text |Cite
|
Sign up to set email alerts
|

Differential alterations in 5α‐reductase type 1 and type 2 levels during development and progression of prostate cancer

Abstract: 5alphaR1 immunostaining is increased and 5alphaR2 immunostaining is decreased during development of PCa. In addition, there is increased expression of both 5alphaR isozymes in recurrent and metastatic cancers, suggesting that both isozymes may be important in the development and progression of PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(103 citation statements)
references
References 29 publications
7
93
1
Order By: Relevance
“…Thomas et al 8 suggested that 5a-R1 is of greater importance in promoting and maintaining prostate cancer as compared to 5a-R2. In an extension of this work, Thomas et al 9 found that 5a-R1 moderate plus high intensity immunostaining was augmented from 4.8% of total epithelial area in BPH to 17% in primary over 38% in recurrent, and 55.8% in metastases of prostate cancer, whereas 5a-R2 showed varying responses. Using semiquantitative reverse transcriptase-PCR it was demonstrated, that 5a-R2 is consistently underexpressed in prostate cancer versus normal or hyperplastic prostates.…”
Section: Methodssupporting
confidence: 51%
“…Thomas et al 8 suggested that 5a-R1 is of greater importance in promoting and maintaining prostate cancer as compared to 5a-R2. In an extension of this work, Thomas et al 9 found that 5a-R1 moderate plus high intensity immunostaining was augmented from 4.8% of total epithelial area in BPH to 17% in primary over 38% in recurrent, and 55.8% in metastases of prostate cancer, whereas 5a-R2 showed varying responses. Using semiquantitative reverse transcriptase-PCR it was demonstrated, that 5a-R2 is consistently underexpressed in prostate cancer versus normal or hyperplastic prostates.…”
Section: Methodssupporting
confidence: 51%
“…3). 21 In contrast, type 2 expression is lower in PIN and primary cancer compared with that in BPH and no different from that in BPH in recurrent and metastatic prostate cancer. Another study has also shown higher type 1 than type 2 expression in recurrent prostate cancer, androgen stimulated benign prostate and androgen stimulated prostate cancer, 22 and a 2.1-fold increase in type 1 expression in metastatic vs primary cancer.…”
Section: Expression Of 5αr In Health and Diseasementioning
confidence: 96%
“…HSD17B3 mRNA was increased over 30 fold in PCa biopsies and the enzyme has been shown to be upregulated 8-fold in LuCaP-23 and LuCAP-35 PCa cell lines, obtained from metastatic tissues of a patient resistant to castration therapy [15,22] SRD5 A1 During PCa development its expression increases. A 2-4 fold increase of SRD5A1 expression, induced by activation of AR, has been observed in three androgen-responsive PCa cell lines [88,89,[178][179][180][181] A2 Predominant isoform expressed in the normal prostate. During PCa development, its expression decreases.…”
Section: Cyp17a1mentioning
confidence: 93%